6xz-5x=

Simple and best practice solution for 6xz-5x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6xz-5x= equation:


Simplifying
6xz + -5x = 0

Reorder the terms:
-5x + 6xz = 0

Solving
-5x + 6xz = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-5 + 6z) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-5 + 6z)' equal to zero and attempt to solve: Simplifying -5 + 6z = 0 Solving -5 + 6z = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 6z = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 6z = 0 + 5 6z = 0 + 5 Combine like terms: 0 + 5 = 5 6z = 5 Add '-6z' to each side of the equation. 6z + -6z = 5 + -6z Combine like terms: 6z + -6z = 0 0 = 5 + -6z Simplifying 0 = 5 + -6z The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

x = {0}

See similar equations:

| 2(a+12)=4 | | 2(x+4)=4+2x | | 18/12=m/42 | | 6d+5d=-11 | | 3x+2-4(8-7)=90 | | 10+x-1/3x+0 | | 35=-5+2g-7g | | b+27.51=36 | | -8n-3=-11 | | b/2-4=-8 | | -8n-3=-10 | | -8n-3=-83 | | x/2-5=-7 | | 2y^2-7y-15= | | 6x+45=9(x+5)-3x | | r/5+2=0 | | x/0.25 | | -1/5p+3/4p=11 | | -y=2(-2)-8 | | w+31=50 | | 2x+y+1=0 | | 6.7+p=10.4 | | 21+d=52 | | 2=n+1-1 | | s+17=38 | | 9x=9y+36 | | 1/3d=-6 | | 34+r=62 | | 25/6+b=10/2 | | 5x+5x=-6+1+6x+3x | | 10y-2=8y-1 | | 36a=32 |

Equations solver categories